If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + y = 27 Solving -11 + y = 27 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + y = 27 + 11 Combine like terms: -11 + 11 = 0 0 + y = 27 + 11 y = 27 + 11 Combine like terms: 27 + 11 = 38 y = 38 Simplifying y = 38
| 2x+12=2x-48 | | 19.9y-9.98=1.29-9.37+20y | | x^2-2ax-3a^2=0 | | -11+38=27 | | 7x+3+8x+6=144 | | -10+8a=6(a-4) | | [2+-3]=-4 | | 54=2x^2+12x | | 5-4x=2-3x | | -8(24)+15=x | | f+11=-9 | | 13=x*1.25 | | 2x+4x-3+10=10x-19 | | X+(-y)=-y+x | | 80=2l+2*14 | | 7=32(5x+8) | | -10.5p=-5-11p | | u=8a-56 | | 7 = 32(5x+8) | | 7e^4x+8=14 | | 6-2n=16 | | 9c-3d=c | | 4b-9b+3=-32 | | ln(x^2)+ln(9)=3 | | 16+5c=-29 | | 7x+6+9x+8=126 | | (9+9)x^2+(-4+8)x-30= | | [-4-3]=1 | | -15=a-40 | | 5x-1=14x-49 | | 2x+3y+5z=1 | | -5+7b+3=33 |